Preliminary Assessment of Agricultural Area and its Influence to the Quality of Water in Golfo Dulce, Costa Rica - Fournier, María Luisa (2019)
With the purpose of designing a quality control program of the waters entering the estuary, a preliminary assessment of agricultural activity was done in the sub-basins Esquinas, Coto Colorado, Rincón, Conte, Agujas, Tigre, and Palma. The extension of the cultivated area was determined through interpretation of satellite images. With secondary information and surveys to producers, the use of pesticides and fertilizers was estimated. A point sampling was done for pesticide residues in water, sediment, and fish. The samples were analyzed with gas chromatography with mass detection and liquid chromatography with a diode array detector. An area of 10,000 ha of rice Oryza sativa and 31,000 ha of oil palm Elaeis guineensis plantations was estimated. Annual use of pesticides was estimated in 20.4 kg ha-1 in rice and 6.6 kg ha-1 in oil palm, and 840 kg ha-1 yr-1 of granulated fertilizers in both crops. The herbicide clomazone was detected in all water samples. Furthermore, in the Coto Colorado sub-basin, which encompasses 95 % of the total agricultural area that drains into the gulf, the insecticide triazophos and fungicides isoprothiolane and propiconazole were also detected. The extension and management of agricultural plantations in the watershed that drains into the Golfo Dulce, in addition to its environmental factors, could pose a threat to the estuary resources. It is advisable to monitor the quality of water in rivers, as well as to develop programs for the restoration of the riparian forests as a mitigation measure.